2007
DOI: 10.1371/journal.pone.0000513
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Substantia Nigra Pars Compacta in Regulating Sleep Patterns in Rats

Abstract: BackgroundAs of late, dopaminergic neurotransmission has been recognized to be involved in the generation of sleep disturbances. Increasing evidence shows that sleep disturbances in Parkinson's disease (PD) patients are mostly related to the disease itself, rather than being a secondary phenomenon. Evidence contained in the literature lends support to the hypothesis that the dopaminergic nigrostriatal pathway is closely involved in the regulation of sleep patterns.Methodology/Principal FindingsTo test this hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
74
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 31 publications
4
74
0
2
Order By: Relevance
“…Accordingly, the neurochemical profile promoted by LPS was comparable to that elicited by MPTP, which is considered a toxin that generates a mild neurodegeneration, even in a repeated intranigral administration protocol [12]. Hence, it is postulated that MPTP particularly model the early phase of PD, which is primarily characterized by the occurrence of cognitive, emotional and sleep deficits, than motor abnormalities [6,8,10,14,21,35]. The neuronal degeneration promoted by 6-OHDA is characteristically more evident at seven days after the neurotoxin administration, however some markers (e.g.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, the neurochemical profile promoted by LPS was comparable to that elicited by MPTP, which is considered a toxin that generates a mild neurodegeneration, even in a repeated intranigral administration protocol [12]. Hence, it is postulated that MPTP particularly model the early phase of PD, which is primarily characterized by the occurrence of cognitive, emotional and sleep deficits, than motor abnormalities [6,8,10,14,21,35]. The neuronal degeneration promoted by 6-OHDA is characteristically more evident at seven days after the neurotoxin administration, however some markers (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, loss of tyrosine hydroxylase immunoreactivity (TH-ir) began in axons at 6 h, and progressed to cell bodies at later time-points post lesion [36]. Similarly, MPTP can cause a short term dopaminergic neurodegeneration with reductions of nigral TH expression as well as TH-ir cell death [4,8,12]. Moreover, a single injection of LPS to the SNpc region of Wistar, Fisher or Sprague-Dawley rats indeed leads to a fast marked loss (50-85%) of SNpc dopaminergic neurons [1,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,33 Furthermore, Takakusaki et al showed that the excessive GABAergic output from the basal ganglia to the PPN in patients with PD may induce sleep disturbances, including a reduction of REM sleep periods and REM sleep behavioral disorders as REM without atonia. 5 Studies in MPTP-treated rats, cats, and monkeys have also reported a role for dopaminergic neurons in the substantia nigra in the regulation of REM sleep, 3,4,34,35 In addition, dopamine D2-receptor immunoreactivity has been found in brainstem structures involved in REM M Zoetmulder, M Nikolic, H Biernat et al Increased EMG-activity is linked to Dopamine in iRBD and PD sleep without atonia, including subcoeruleus, lateral paragigantocellular, nucleus raphe magnus, gigantocellular nucleus pars alpha, ventral gigantocellular nucleus, and raphe obscurus. 33,36 We found significant inverse correlations between 123 I-FP-CIT uptake and non-periodic EMG activity in the mentalis and tibialis muscle in PD patients with RBD during NREM sleep.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that the dopaminergic system is associated with sleep-wake disturbances. 3,4 Previous studies have shown that basal ganglia structures, such as the substantia nigra pars reticulata and the internal segment of the globus pallidus, have caudal connections to regions that modulate REM sleep atonia. 5 Imaging studies in iRBD patients have shown microstructural changes in substantia nigra, 6 reduced volume of the putamen, 7 as well as reduced density of the striatal dopamine transporter, which decreases in the course of disease progression.…”
Section: Introductionmentioning
confidence: 99%